Noble metal-free catalytic decarboxylation of oleic acid to n-heptadecane on nickel-based metal–organic frameworks (MOFs). Issue 14 (15th June 2017) - Yang, L.; McNichols, B. W.; Davidson, M.; Schweitzer, B.; Gómez-Gualdrón, D. A.; Trewyn, B. G.; Sellinger, A.; Carreon, M. A.
Abstract : Herein we demonstrate novel noble metal-free catalytic systems based on Ni MOFs that can effectively convert oleic acid into heptadecane. Abstract : Nickel based metal organic frameworks (Ni-MOFs) were successfully synthesized using new conjugated carboxylic acid linkers. These conjugated carboxylic acid linkers were synthesized using mild Heck coupling that led to the incorporation of functional groups not possible by traditional synthetic methods. Control of linker size allows for porosity tuning of the crystalline network and high surface area, that, in theory, results in the increased accessibility to Ni metal centers for catalysis. The resultant crystalline Ni-MOFs displayed BET areas as high as ∼314 m 2 g −1 . To investigate their catalytic activity for conversion of oleic acid to liquid hydrocarbons, Ni-MOFs were grown on zeolite 5A beads that served as catalytic supports. The resultant catalysts displayed heptadecane selectivity as high as ∼77% at mild reaction conditions, one of the highest yields for non-noble metal containing catalysts. The catalytic activity correlated to the concentration of acid sites. A slight decrease in catalytic activity was observed after catalysts recycling.